أساليب إستغلال العقار الوقفي في التشريع الجزائري - إسماعيل عيدودي; منال سردوك (My University, 2022)
Summary of note: Given the active role and the critical importance of the moratorium in economic and social terms on the one hand as well as seeking solidarity among members of society, The Islamic Shari 'a guaranteed and recommended by the Algerian legislature and guaranteed protection by adhering to a special law that safeguards the moratorium in general and the moratorium on land in particular, for the many in Algeria on the one hand, as well as for the developmental role played by the latter. This requires the legislator to develop effective mechanisms and methods to ensure the lawmaker's proper exploitation and achievement of his purpose, as well as to develop his rents and ensure his sustainability. ……………………. ملخص المذكرة: نظراً للدور الفعال والأهمية البالغة للوقف من الناحية الإقتصادية والإجتماعية من جهة، وكذا سعيه لتحقيق التكافل بين أفراد المجتمع من جهة أخرى، فقد كفلته الشريعة الإسلامية و أوصت به كما تبناه المشرع الجزائري وكفل له حماية وذلك بتنضيمه في قانون خاص يصون الوقف بصفة عامة والوقف العقاري بصفة خاصة وذلك لكثرته في الجزائر من جهة، وكذا للدور التنموي الذي يلعبه هذا الأخير. الأمر الذي أوجب على المشرع إستحداث آليات وأساليب فعّالة لضمان حسن إستغلاله وتحقيق الغاية منه وكذا لتنمية ريعه وضمان ديمومته. ……………………. Résumé de la note : Compte tenu du rôle actif et de l’importance critique du moratoire en termes économiques et sociaux, d’une part, et de la recherche de la solidarité entre les membres de la société, d’autre part, La Charia islamique garantie et recommandée par le législateur algérien et garantie la protection en adhérant à une loi spéciale qui protège le moratoire en général et le moratoire sur la terre en particulier, pour beaucoup en Algérie d’une part, ainsi que pour le rôle de développement joué par ce dernier, ce qui oblige le législateur à développer des mécanismes et des méthodes efficaces pour assurer la bonne exploitation et la réalisation de son but par le législateur, ainsi que pour développer ses rentes et assurer sa pérennité.